2017
DOI: 10.3390/rs9030258
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Feature Tracking and Pattern Matching with Optimal Parametrization for Sea Ice Drift Retrieval from SAR Data

Abstract: Sea ice drift strongly influences sea ice thickness distribution and indirectly controls air-sea ice-ocean interactions. Estimating sea ice drift over a large range of spatial and temporal scales is therefore needed to characterize the properties of sea ice dynamics and to better understand the ongoing changes of the climate in the polar regions. An efficient algorithm is developed for processing SAR data based on the combination of feature tracking (FT) and pattern matching (PM) techniques. The main advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…This important region of the world ocean will not be well monitored in terms of currents by existing and planned satellite missions. Ice concentration is the 5 only parameter that is well monitored near the ice edge, with difficulties in recovering ice thickness and ice drift (Korosov and Rampal, 2017). The very rich dynamics across the ice edge offer great opportunities for Doppler-based measurements.…”
Section: Challenges and Opportunities Over Sea Icementioning
confidence: 99%
“…This important region of the world ocean will not be well monitored in terms of currents by existing and planned satellite missions. Ice concentration is the 5 only parameter that is well monitored near the ice edge, with difficulties in recovering ice thickness and ice drift (Korosov and Rampal, 2017). The very rich dynamics across the ice edge offer great opportunities for Doppler-based measurements.…”
Section: Challenges and Opportunities Over Sea Icementioning
confidence: 99%
“…We also plan to test the benefits of assimilation of SAR-derived ice drift (Korosov and Rampal, 2017) on the system.…”
Section: Discussionmentioning
confidence: 99%
“…The landmask has a resolution of 250 m. The absolute location accuracy of the medium-resolution EWS product is not specified in the User's Manual. For the IWS mode it is 7 m. Korosov and Rampal [20] found that the accuracy of georeferencing was about 5 pixels (i.e., 200 m) for the EWS medium resolution product.…”
Section: Datamentioning
confidence: 99%